ANALYTICAL STUDY OF SADHAKS UNDER YOGA PHILOSOPHY - Suryavanshi, Krishna; Beg, Mirza Fahim; Sharma, Nikhil (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The totality of the goal, means and sadhak’s tools is sadhana, whose ultimate goal is surrender to the Supreme Being. Sadhana transforms the sadhak from a human to a great human and from a living soul to the form of the Supreme Being. For this state, names like Moksha, Kaivalya, Nirvana, and Samadhi are mentioned in various texts. To achieve this state, different sects have propounded different views and paths. The person who progresses by following these steps is addressed as a Sadhak. In fact, despite the similarity in the goals of all the Sadhaks, there is a difference in them on the basis of the methodology of different sects and streams. In different Upasakas like Kutichak, Bahudak, Hans, Paramhans, Arta, Artharthi, Jigyasu and Gyani, there is mention of Mridu, Ma, Dhya, Adhimaatra and Adhimaatratva Sadhaks in different categories and Mantra, Laya, Hatha, Raj, Gyan, Bhakti and Karmayoga in different streams. Among these, the Sadhaks who have attained the ultimate state of Sadhana, Adhyatmapad, have been referred to in the spiritual texts by the names of Digambar, Turiyatit, Avdhoot, Adhimaatratam, Gyani, Sthitapragya and Jeevanmukt etc. In Yoga Darshan, the practitioners striving to achieve this state have been instructed to follow various vows such as Ashtang Yoga, Kriya Yoga, practice-vairagya and Ishwar Pranidhan etc. In following these vows, the essentiality of desirability of qualities like stability, eternity, continuity, dedication and love is considered important. In society, they are generally addressed as Sadhu, Saint, Sanyasi, Bhakt, Bhikshu, Yogi and Tapasvi etc. Sadhaks often promote public welfare along with self-improvement.